Instalación y evaluación de un sistema de riego por goteo en el sistema agroforestal con café (Coffea arabica L.) en la Quinta Experimental “La Argelia” de la provincia de Loja - Rosales Torres, Gina Vanessa (2024)
Irrigation is a vital component for food sovereignty, since it plays a fundamental role in economic and social development. Its influence is evident in improving the socioeconomic conditions of farmers and peasants in Ecuador. In this context, the study entitled "Installation and evaluation of a drip irrigation system in the agroforestry system with coffee (Coffea arabica L.) in the Quinta Experimental "La Argelia" in the province of Loja" aims to promote the efficient use of water in agriculture, especially in the coffee plantations of the Quinta Experimental through the implementation and evaluation of drip irrigation. The research was structured in two phases. First, the installation of the drip irrigation system, which included the preparation and excavation of trenches, the layout of the system, the installation of the irrigation and fertigation head, and its connection to the piping lines. Once the installation was completed, the second phase consisted of evaluating the operation and uniformity of application, which was divided into two stages. The first was based on detecting possible leaks or damage to the components. In the second, the methodology of Merriam and Keller (1978), modified by Chamba (2020), was followed, obtaining a value of 91% in the distribution efficiency, Christiansen uniformity coefficient and application efficiency, respectively, indicating a satisfactory uniformity and efficiency of the irrigation method. In addition, a comprehensive manual was prepared for the management, operation and maintenance of the irrigation system. This manual detail the description of the system, the correct operation of its components and the necessary maintenance to ensure its efficiency and useful life. With these actions, the objective is to offer a technified irrigation alternative that contributes to the sustainable progress of the coffee crop implemented in the study area.